Teaching Poetry by Using CBLT - *, Siswantoro (Sebelas Maret University, 2016)
Poetry is the most neglected subject in the teaching of English as a Second Language. Being neglected forlong, it has become a peripheral item. Unlike reading and speaking it is minor n the major trends. No wonderteachers and students are not familiar with it. Therefore they do not know how to interact with a poemsystematically. The major cause is the lack of competence in its convention. Culler states anyone lacking in it, would be quitebaffled if presented with a poem. Like structure, it serves as the underlying system.Arbitrarily it is a set of rules. To be able to interact with poetry, students have to provide themselves with itthe way a poet does. It covers (1) figures of speech covering simile, metaphor, hyperbole, etc. (2) rhythmcovering: syllable, foot, metre (3) meaning related to autonomy, theories developed on the back of the NewCriticism, semiotic theories developed under the influence of the discipline of theoretical linguistics, andinternationalist theories inspired by speech-act theory and Grecian analysis of meaning; and (4) poem formscovering ballad, sonnet, free verse, etc.As the complex whole, poetry cannot be taught wholly at a time. It is broken into smaller parts called units ofcompetence. Through the graded goals, the whole communicative competence will be achieved incrementally.Teaching Poetry by Using CBLT